2013
DOI: 10.4238/2013.february.19.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotypic diversity of cervical human papillomavirus infection among women from an urban center in Brazil

Abstract: ABSTRACT. Human papillomavirus (HPV) infection is a common viral sexually transmitted infection and the main cause of cervical cancer in women worldwide. Epidemiological data on the prevalence of HPV in a given population is essential for the establishment of effective prevention strategies. The aim of this study was to determine HPV prevalence in women who attended a public health service within an urban center in Brazil. Cervical samples were collected from 337 women recruited from a primary public health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(37 reference statements)
5
11
0
5
Order By: Relevance
“…Our result was similar to that described by the Latin America Screening Study (24.5%) [8] and to data related to Amazonas State (29.2%) [18]. However, it was lower than described in others Brazilian studies including women populations from Rio Grande do Sul (34%), São Paulo (58.4%), Distrito Federal (62%) and Rio de Janeiro (63.6%) [19-21]. …”
Section: Discussionsupporting
confidence: 89%
“…Our result was similar to that described by the Latin America Screening Study (24.5%) [8] and to data related to Amazonas State (29.2%) [18]. However, it was lower than described in others Brazilian studies including women populations from Rio Grande do Sul (34%), São Paulo (58.4%), Distrito Federal (62%) and Rio de Janeiro (63.6%) [19-21]. …”
Section: Discussionsupporting
confidence: 89%
“…In South America, Brazil has the highest incidence of cervical cancer, with a prevalence of HPV infection among women with normal cervical cytology of 21.1%, being the northern and northeastern regions with higher mortality than eastern and southern states (Dutra et al , 2012). In another study developed in Rio Grande do Sul state, the prevalence of HPV-DNA found in women with normal cytology was of 32.7% (Coser et al , 2013). It is reasonable to assume that these differences in HPV prevalence can be due to risks factors associated to the characteristics of populations in different countries, sensibility of the study method used to detect DNA, and/or the number of women included in each study (sample size).…”
Section: Discussionmentioning
confidence: 99%
“…É aventado que a introdução dessa imunização talvez possa modificar o equilíbrio já estabelecido da distribuição dos genótipos 28 . Nesta amostra, a taxa de infecção por múltiplos genótipos foi semelhante à relatada por Adler et al 29 (68%), porém muito superior ao encontrado em Ouro Preto (27%) 17 e Rio Grande do Sul (16,7%) 13 . A prevalência da infecção pelo HPV e das infecções múltiplas descritas nos estudos entre 1990 e 2010 aumentou significativamente 25 .…”
Section: Discussionunclassified
“…Os resultados sobre a distribuição dos genótipos de HPV no Brasil são mais modestos, e os estudos são concentrados nos estados da região Sudeste 9 . Em concordância com as observações mundiais, o HPV 16 foi o tipo mais frequente em pesquisas realizadas em diferentes regiões do país [10][11][12][13][14][15][16][17][18] . Entretanto, a heterogeneidade na distribuição é encontrada principalmente em relação aos demais tipos [5][6][7][8]19,20 .…”
Section: Introductionunclassified
See 1 more Smart Citation